The SESAME materials science beamline for XRD applications. (30th January 2017) - Abdellatief, M.; Rebuffi, L.; Khosroabadi, H.; Najdawi, M.; Abu-Hanieh, T.; Attal, M.; Paolucci, G.
Abstract : We present a detailed description of the SESAME Materials Science (MS) beamline for X-ray diffraction (XRD) applications, presently under construction in Allan, Jordan. The beamline is based on components previously installed at the Swiss Light Source, but modifications in the beamline design have been introduced to match the characteristics of the SESAME storage ring. The SESAME MS beamline will accommodate XRD experiments in the energy range between 5 and 25 keV. The beamline ray tracing analysis at 10 keV estimates the flux at the sample to be of the order of 10 13 (photons s −1 ), the energy resolution is about 2 eV and the effective beam size at the sample of 300 × 2800 µm 2 . Investigations of microstruture will be possible as the instrumental broadening, resulted from simulating the diffraction pattern for a standard material, is of the order of 0.01° at 15 keV. A wide range of applications will be possible at the beamline, such as powder diffraction studies, single crystals and in situ XRD. The commisioning of the beamline is expected to be in the second half of 2017.